2021
DOI: 10.1038/s41419-021-04269-4
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circUBE2J2 acts as the sponge of microRNA-370-5P to suppress hepatocellular carcinoma progression

Abstract: Accumulating evidences indicate that circular RNAs (circRNAs), a class of non-coding RNAs, play important roles in tumorigenesis. However, the function of circRNAs in hepatocellular carcinoma is largely unknown. CircRNA microarray was performed to identify abnormally expressed circRNAs in HCC tissue samples. We conducted Kaplan–Meier survival analysis to explore the significance of circUBE2J2 in clinical prognosis. Then, we examined the functions of circUBE2J2 in HCC by cell proliferation, migration, and mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
(37 reference statements)
0
13
0
Order By: Relevance
“…In this study, miR-370-5p was identified as a target of CHRM3-AS2 in glioma. miR-370-5p is an anti-oncogene that has been reported to be down-regulated in breast, lung, liver, and ovarian cancers (20)(21)(22)(23). Decreased expression of miR-370-5p was consistently observed in glioma cells.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In this study, miR-370-5p was identified as a target of CHRM3-AS2 in glioma. miR-370-5p is an anti-oncogene that has been reported to be down-regulated in breast, lung, liver, and ovarian cancers (20)(21)(22)(23). Decreased expression of miR-370-5p was consistently observed in glioma cells.…”
Section: Discussionmentioning
confidence: 97%
“…Li et al found that overexpression of miR-370-5p inhibits cell proliferation, migration, and invasion and induces cell-cycle arrest in nonsmall-cell lung carcinoma cells (21). Zhang et al (22) revealed that knockdown of miR-370-5p enhances the proliferative and invasive rates of colorectal cancer cells. As miR-370-5p expression is downregulated by CHRM3-AS2, we suspect that the anti-tumour effect of CHRM3-AS2 silencing in glioma cells is associated with the upregulation of miR-370-5p expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… CircRNAs are implicated in disease development via sponging miRNAs. For instance, circUBE2J2 reduced migration and proliferation of hepatocellular carcinoma cells via controlling miR-370-5p [ 26 ]. CircRNA ubiquitin-specific protease 34 (circUSP34) exacerbated cell malignant behaviors of osteosarcoma by inhibiting miR-16-5p [ 27 ].…”
Section: Discussionmentioning
confidence: 99%